2015
DOI: 10.3109/19401736.2015.1053129
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of Tenthredo tienmushana (Takeuchi) and a related phylogenetic analysis of the sawflies (Insecta: Hymenoptera)

Abstract: The mitochondrial genome sequence of Tenthredo tienmushana (Takeuchi, 1940) (Hymenoptera: Tenthredinidae) (GenBank accession KR703581) was reported. The length of the sequenced region of this mitochondrial genome is 14,943 bp, with 13 protein-coding, two rRNA, 19 tRNA (the trnI, trnQ, and trnM were failed to sequence) genes and a partial A + T-rich region. As in most other sequenced mitochondrial genomes of the suborder "Symphyta", there is no gene rearrangement in the sequenced region compared with the pupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…A very short A + T‐rich region (e.g., ~200 bp ) is uncommon in Hymenoptera. We subsequently reexamined all available hymenopteran A + T‐rich regions and found that those of Trichiosoma anthracinum (Tenthredinoidea), Tenthredo tienmushana (Tenthredinoidea), and Monocellicampa pruni (Tenthredinoidea) were 100 bp , 66 bp , and 132 bp long, respectively (Wei et al ; Song et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…A very short A + T‐rich region (e.g., ~200 bp ) is uncommon in Hymenoptera. We subsequently reexamined all available hymenopteran A + T‐rich regions and found that those of Trichiosoma anthracinum (Tenthredinoidea), Tenthredo tienmushana (Tenthredinoidea), and Monocellicampa pruni (Tenthredinoidea) were 100 bp , 66 bp , and 132 bp long, respectively (Wei et al ; Song et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, the mitogenome characteristics of Cephinae were summarized by combining five new nearly complete mitogenomes representing two tribes: Hartigiini ( J. compressus , H. linearis and S. parreyssi ) and Pachycephini ( P. smyrnensis and P. cruentatus ). Compared with reported symphytan mitogenomes (Castro & Dowton, ; Dowton et al ., ; Song et al ., , ; Wei et al ., , ), Cephinae mitogenomes share features such as A + T bias base composition and codon usage bias (Table S4). However, several striking features are observed in Cephinae.…”
Section: Discussionmentioning
confidence: 99%
“…Some additional COI sequences representing broad diversity of Tenthredinidae, Cimbicidae, Diprionidae, and Heptamelus , and which were at least 1000 bp long, were downloaded from NCBI nucleotide database (http://www.ncbi.nlm.nih.gov/nucleotide). The downloaded sequences were published previously by Prous et al 2011, Boevé et al 2013, Wei et al 2015a, Wei et al 2015b, Malm and Nyman 2014, and Song et al 2015. Only the downloaded COI sequence of Eupareophora parca was shorter than others (KF528474; 862 bp), because this was the only Eupareophora sequence publicly available.…”
Section: Methodsmentioning
confidence: 99%